Errors in the use of Verbs Caused by the Interference of Bahasa Indonesia as the First Language in the Writing of Final Project Abstracts Done by the Batam Polytechnic Students - Erikson Togatorop; Aguak Aguak; Arieyanto Arieyanto; Denny Boy Tampubolon; Dedi Chandra; Karel Steviano; Rina Hetti Sitorus; Subiyantoro Subiyantoro; Pancur Manurung; Rizkia Yuva Batam Via Siregar; Hilarius Roni Setiawan; Tio Lukas; David Santoso; Nova Ade Saputra; Deni Arsenal (Politeknik Negeri Batam, 2010)
Polytechnic is one of the colleges that requires the writing of the final project as one of the important graduation requirements for its students in the end of their three years study. Batam Polytechnic, as a college located in the region which directly borders with Singapore and Malaysia and whose graduates are mostly employed by multinational companies encourages its students to write their final project abstracts in English. This research was done to investigate the errors in the use of verbs in the final project abstracts done by the Batam Polytechnic students. The result of this inquiry is assumed to reveal the properness level of the English abstract of the final project in Polytechnic. Besides, it is also supposed to contribute to determine the standard of the final project writing in Polytechnic, especially in writing its English abstract.